EFEKTIVITAS PENERAPAN E-COURT DALAM PERKARA WANPRES-TASI DI TINJAU DARI PERMA NO 1 TAHUN 2019 (Studi Penelitian Pengadilan Negeri Singkil) - Susanti, Susanti; Jalaluddin, Jalaluddin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The Singkil District Court has now implemented this regulation before the existence of Covid-19 in Indonesia. However, the fact that it was found that the electronic trial process at the Singkil District Court, especially in cases of default, was still not effectively carried out due to several obstacles experienced so that the trial process could not be applied due to the principle of speed. This study aims to examine the effectiveness of implementing defaults based on PERMA No. 1 of 2019, in the field of civil law and find out what obstacles and solutions are experienced by the litigants in the Singkil District Court. The research method used is empirical research, namely by using facts obtained through interviews and looking at real behavior through direct observation. The results of the study show that the application of E-court in PERMA No. 1 of 2019 in default cases at the Singkil District Court has not been fully implemented, because there are many obstacles that hinder electronic trials in default cases so that the trial process is very slow. It can be concluded that the application of E-court in default cases at the Singkil District Court is not fully in accordance with PERMA No 1 of 2019.